The international diplomacy of Israel's Founders : deception at the United Nations in the quest for Palestine - Quigley, John B. (Cambridge : Cambridge University Press, 2016)
During the early to mid-twentieth century, the Zionist Organization secured a series of political victories on the international stage, leading to the foundation of a Jewish state and to its ability to expand its territorial control within Palestine. The International Diplomacy of Israel's Founders provides a revisionist account of the founding of Israel by exposing the misrepresentations and false assurances of Zionist diplomats during this formative period of Israeli history. By comparing diplomatic statements at the United Nations and elsewhere against the historical record, it sheds new light on the legacies of such leaders as Chaim Weizmann, David Ben Gurion, Abba Eban, and Shabtai Rosenne. Including coverage of little-discussed moments in early Israeli history, this book offers an important new perspective for anyone interested in the history of the Israeli-Palestinian conflict.
Machine generated contents note: 1. A public relations imperative; 2. Promises, promises; 3. Pranks in Paris and Geneva; 4. Courting the commissar; 5. Saving Europe's Jews -- our way; 6. Smoke and mirrors at the YMCA; 7. The ship that launched a nation; 8. Cocktails at the consulate; 9. Causing chaos; 10. Denying the undeniable; 11. A peace-loving state?; 12. Joining the world with fingers crossed; 13. Israel 1, United Nations 0; 14. A phantom attack; 15. Sabras in Sinai: pardon my French; 16. Suez smoke-screen; 17. Mr Nasser, please attack; 18. Abba Eban's finest hour; 19. Old issues, new lies; 20. An organization turned sinister; 21. Prevarication pays.
Title from publisher's bibliographic system (viewed on 07 Jan 2016).
Keywords: United Nations -- Israel -- History -- 20th century; Israel -- Foreign relations; Palestine -- History -- Partition, 1947.; Arab-Israeli conflict; Propaganda, Israeli; Propaganda, Zionist